Comparison between two culture media for in vitro evaluation of antifungal susceptibility of the Sporothrix schenckii complex Comparação entre dois meios de cultura para avaliação in vitro da suscetibilidade a antifúngicos do complexo Sporothrix schenckii - Cheila Denise Ottonelli Stopiglia; Daiane Péres Marchese; Daiane Heidrich; Julia Medeiros Sorrentino; Fabiane Jamono Vieira; Maria Lúcia Scroferneker (Sociedade Brasileira de Dermatologia, 2012)
BACKGROUND: The standard methodology for determining the antifungal sensitivity against the Sporothrix schenckii complex recommends the use of the 1640 Roswell Park Memorial Institute culture medium (RPMI) buffered with morpholinepropanolsulfonic acid (MOPS). However, while this is a high-cost medium which requires a laborious implementation and sterilization by filtration, the Sabouraud dextrose broth is a low-cost medium, widely used in mycology, sterilized by autoclave. OBJECTIVE: To evaluate the performance of the Sabouraud dextrose broth culture medium as a substitute for the RPMI 1640-MOPS in determining the antifungal sensitivity of S. schenckii. METHODS: Forty-eight clinical isolates were evaluated against five antifungal agents: itraconazole, ketoconazole, fluconazole, amphotericin B and terbinafine, using the method of broth microdilution advocated by the M38-A2 protocol of the Clinical and Laboratory Standards Institute. RESULTS: There were no significant differences between the Minimum Inhibitory Concentrations obtained in the two culture media for all the antifungals, with the exception of the amphotericin B. Regarding this drug, the Minimum Inhibitory Concentration range obtained were wider for the Sabouraud dextrose broth than for the Roswell Park Memorial Institute morpholinepropanelsulfonic acid. CONCLUSIONS: The Sabouraud dextrose broth showed potential to be used in the in vitro evaluation of the S. schenckii complex antifungal activity. FUNDAMENTOS: A metodologia padronizada para a determinação da sensibilidade aos antifúngicos frente ao complexo Sporothrix schenckii preconiza a utilização do meio de cultura Roswell Park Memorial Institute (RPMI) 1640 tamponado com ácido morfolinopropanosulfônico (MOPS). No entanto, este meio possui custo elevado, execução trabalhosa e esterilização por filtração. Já o caldo Sabouraud-dextrose é amplamente utilizado em micologia, de baixo custo e pode ser esterilizado por autoclavagem. OBJETIVO: Avaliar o desempenho do meio de cultura caldo Sabouraud-dextrose em substituição ao RPMI 1640-MOPS na determinação da sensibilidade de S. schenckii a antifúngicos. MÉTODO: Foram avaliados 48 isolados clínicos frente a cinco antifúngicos: itraconazol, cetoconazol, fluconazol, anfotericina B e terbinafina, utilizando a metodologia da microdiluição em caldo preconizada pelo protocolo M38-A2 do Clinical and Laboratory Standards Institute. RESULTADOS: Não houve diferenças significativas nas Concentrações Inibitórias Mínimas obtidas nos dois meios de cultura para todos os antifúngicos, com exceção da anfotericina B. Para este fármaco, foram obtidas faixas mais amplas de Concentrações Inibitórias Mínimas para caldo Sabouraud-dextrose do que para Roswell Park Memorial Institute-morfolinopropanosulfônico. CONCLUSÕES: O caldo Sabouraud-dextrose mostrou potencial para ser utilizado na avaliação in vitro da atividade antifúngica do complexo S. schenckii.